Pokémon. Sun & Moon. 10 - Kusaka, Hidenori; Turnage, Bryant (VIZ Media, LLC, 2021)
After finding themselves stuck in a alternate dimension, Sun and Moon must help their new friends protect the eternally dark city of Ultra Megalopolis. But a terrible betrayal stops them from getting home.